1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Using one-sided axioms to show <G,*> is a group

  1. Sep 26, 2007 #1


    User Avatar

    1. The problem statement, all variables and given/known data

    Prove that a set G, together with a binary operation * on G, satisfying the
    following three axioms:
    A1) The binary operation * on G is associative
    A2) There exists a left identity element e in G such that e*x=x for all x in G
    A3) For each a in G, there exists a left inverse a' in G such that a'*a=e
    is a group

    2. Relevant equations

    Our definition of a group:

    A group is a set G, and a closed binary operation * on G, such that
    the following axioms are satisfied:
    G1) * is associative on G
    G2) There is an element e in G such that for all x in G
    x*e = e*x = x (existence of an identity element e for *)
    G3) Corresponding to each a in G there is an element a' in G such that
    a*a' = a'*a = e (existence of inverse a' of a)

    3. The attempt at a solution

    G1, is given by A1

    By A2 we know e*x=x for all x in G.
    We must show x*e=x for all x in G to finish proving G2.

    x*e=x, what is to be proved
    x'*(x*e)=x'*x, we know x' exists from A3, existence of inverse
    (x'*x)*e=e, using A1, associativity
    e*e=e, using A3, existence of inverse
    e=e, therefore x*e=x for x in G proving G2 holds.

    By A3 we know there exists x' in G such that x'*x=e for all x in G.
    We must show x*x'=e for all x in G to finish proving G3.

    x*x'=e, what is to be proved
    (x'*x)*x'=x'*e, using A1, associativity
    e*x'=x', using the above theorem
    x'=x', therefore x*x'=e for x in G proving G3 hold.

    Therefore the set G, together with a binary operation * on G, satisfying
    A1, A2 and A3 is a group.

    4. My questions

    Does ending with the e=e statement or x'=x' statement show the original statement holds? Since it ends up with LHS=RHS I think it does but maybe I should try to string statements in the form e*x = ... = x*e although I am not sure why that would be better. I guess it is just what I am used to seeing.

    Also, I skipped the part about the binary operation being closed for a group. Kind of important, I know. I think (hope) it was indirectly mentioned in the axioms when it was stated * in associative -on- G. Is this correct or is it something I will also need to prove? If so, any ideas?

    Thank you for taking the time to read all this.
  2. jcsd
  3. Sep 26, 2007 #2
    "Does ending with the e=e statement or x'=x' statement show the original statement holds?"

    No, you've only shown that e=e and x'=x'...profound statements but not what you set out to show. Here's a hint: x' is in G so x' also has a left inverse...what is it?

    As for the closure, I am unsure. I don't see how one could show the operation is closed without more information about the nature of the group.
  4. Sep 26, 2007 #3


    User Avatar
    Staff Emeritus
    Science Advisor

    Doesn't the phrase "binary operation on G" (as opposed to "binary operation from G to H") imply the operation always gives a value in G? In other words, can't you take closure as "given" by the hypotheses?
  5. Sep 26, 2007 #4


    User Avatar

    I think understand what you are trying to tell me and unfortunately I don't think I even showed e=e and x'=x' since I started from unproved statements. I'll work with your suggestion now and see what I can come up with.

    I was thinking that too but I wasn't positive. Specifically I wasn't sure if on and onto were equivalent. I kind of suspected they were as my text seems to use it that way, but it doesn't explicity state it.

    Thank you guys for the replies.
  6. Sep 26, 2007 #5


    User Avatar
    Science Advisor
    Homework Helper
    Gold Member

    It's not hard, but you gotta start at the right place or you're gonna try for a long god damn time. The right place to start is first with the inverse business. You're gonna try to show that the left inverse of each element in also a right inverse. And for this, you're gonna start with the equation


    Then showing the left identity is also a right identity is easy.
  7. Sep 27, 2007 #6


    User Avatar

    Wow quasar987, you were not kidding about the long god damn time. I spun on this for almost two hours. But when I combined your approach and mcampbell's approach I think I have a proof that works.

    Proof of right inverse

    As x' is in G by A3 there exists an inverse, say x'', such that x''*x'=e

    Thus x'*x = e, and x''*x'=e
    setting them equal to eachother
    x' * x = x'' * x'
    x' * x = x'' * e * x'
    x' * x = x'' * x' * x * x'
    x' * x = e * x * x', by associativity and left identity
    x' * x = x * x' = e

    And the right identity follows easily.
    Thank you guys so much. This problem is going to give me nightmares. So simple but so hard at the same time.
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Similar Discussions: Using one-sided axioms to show <G,*> is a group
  1. Groups Axioms (Replies: 12)